Microelectronics: Biomimetic Microelectronics for Regenerative Neuronal Cuff Implants (Adv. Mater. 43/2015). (November 2015) - Karnaushenko, Daniil; Münzenrieder, Niko; Karnaushenko, Dmitriy D.; Koch, Britta; Meyer, Anne K.; Baunack, Stefan; Petti, Luisa; Tröster, Gerhard; Makarov, Denys; Schmidt, Oliver G.
Abstract : Biomimetic microelectronics are a unique class of devices combining the mechanical adaptivity of soft actuators with the imperceptibility of microelectronics. Due to their inherent ability to self‐assemble, biomimetic microelectronics can be firmly yet gently attached to an inorganic or biological tissue, enabling enclosure of, for example, nerve fibers, or guiding the growth of neuronal cells during regeneration, as presented by D. Karnaushenko, D. Makarov, and co‐workers on page 6797.